Methods of introducing additive technologies into the educational process in the training of future graphic designers - N. Derevyanko; O. Zalevska (Mukachevo State University, 2023)
Additive technologies provide many opportunities for improving activities in various fields, but the specifics of exploring their work and application in the educational process of students enrolled in design education programmes have been understudied. The purpose of this study is to develop methods of implementing additive technologies in the educational process of training future graphic designers and to test their effectiveness. To achieve this purpose, the research methodology used was a mixed-methods study. The study involved students and teachers of Khortytsia National Academy. Through video conferencing and discussions between teachers, the implementation of the "Additive Technologies" course in the educational process (study of 3D printing and modelling) and ways to use additive technologies in other subjects were developed and agreed upon. It was established that before the experiment, students had virtually no experience in learning or working with additive technologies, which was the foundation for the course curriculum. The students' assessment of the quality of learning on the scale "The instructional materials motivation survey" before and after the experiment was examined. A questionnaire has been developed to explore students' opinions on the effectiveness of using additive technologies in the work of a graphic designer, and their impressions of the methods of introducing additive technologies into the educational process. The survey found that the majority of students highly appreciated the impact of using additive technologies in the work of a graphic designer and believe that their study is necessary for effective learning and work in the future. In addition, students highly appreciated the teachers' ability to use additive technologies in the learning process. The methods of introducing additive technologies proposed in the study can be used in the training of higher education students in the field of 02 - Art, considering the specifics of the curriculum. In addition, there are prospects for using additive technologies to perform design work, internships using additive technologies, and defending qualification projects with real-time object manufacturing.